2019
DOI: 10.1111/bjd.18094
|View full text |Cite
|
Sign up to set email alerts
|

Declining incidence of keratinocyte carcinoma in organ transplant recipients

Abstract: This summary relates to https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…The reduction in the risk of SCC in our study is consistent with the results of a Norwegian nationwide cohort study 17 . A recent study in Ireland reported significant reduction over the past two decades in the incidences of both post‐transplant SCC and BCC 18 …”
Section: Discussionsupporting
confidence: 91%
“…The reduction in the risk of SCC in our study is consistent with the results of a Norwegian nationwide cohort study 17 . A recent study in Ireland reported significant reduction over the past two decades in the incidences of both post‐transplant SCC and BCC 18 …”
Section: Discussionsupporting
confidence: 91%
“…With the prevalence of BCC and SCC (including Bowen’s disease) being 13 and 30%, the SCC/BCC ratio was 2.6/1, similar to that in other studies in SOTRs, that is, an approximate reversal of the ratio of 1/4 found in the general population [3, 4, 9]. The prevalence of actinic keratosis and skin cancer has recently been reported to be high in Australian lung transplant recipients, [10] although the risk of skin cancer following solid organ transplantation in European countries has been shown to be declining over the last decades [11, 12].…”
Section: Discussionsupporting
confidence: 80%
“…Organ-transplant recipients (OTRs) have a dramatically increased risk of keratinocyte cancers (KCs), especially basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), compared with the general population. They have up to seven times increased risk for BCC and between 20 and 100 times for SCC compared with the general population (Garrett et al, 2017;Lowenstein et al, 2017;Menzies et al, 2019;Park et al, 2019).…”
Section: Introductionmentioning
confidence: 99%